Genus-group names of Mutillidae (Hymenoptera): corrections and updates since 2008 - Brothers, Denis J.; Lelej, Arkady S.; Williams, Kevin A. (Zootaxa, 2019)
Information is provided for 38 genus-group names in Mutillidae, of which 13 have been proposed as new since 2008. For 14 names, additional information is provided beyond that given in Lelej & Brothers (2008), including a new synonymy (Cameronilla Lelej in Lelej & Krombein, 2001 = Spilomutilla Ashmead, 1903). One additional nomen nudum and ten additional incorrect spellings discovered since 2008 are also included. Corrections to the dating and/or numbering of references and addition of references found to have been omitted in the earlier paper are also provided.